2016
DOI: 10.1007/s10067-016-3183-3
|View full text |Cite
|
Sign up to set email alerts
|

Body mass index and response to tocilizumab in rheumatoid arthritis: a real life study

Abstract: Several studies have suggested that obesity could have a negative effect on response to anti-tumor necrosis factor α (anti-TNFα) in rheumatoid arthritis (RA). Little is known about the impact of body mass index (BMI) on other biologic agents. We aimed to evaluate the effect of BMI on response to tocilizumab (TCZ) in RA. RA patients treated with TCZ were included in this multicenter retrospective study. BMI was calculated at the initiation of treatment. After 6 months of treatment, change from baseline in DAS28… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
31
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(35 citation statements)
references
References 32 publications
3
31
0
1
Order By: Relevance
“…A negative association was found between BMI and response to anti‐TNFα therapies, notably infliximab, in RA , psoriatic arthritis and ankylosing spondylitis , which suggests that fat mass may affect the response to biologic agents. Conversely, two recent studies showed that response to TCZ in patients with RA was not affected by baseline BMI . We focused on the relationship between BMI and response to ABA in RA treatment and found no association of increased BMI and low response to ABA.…”
Section: Discussionmentioning
confidence: 74%
“…A negative association was found between BMI and response to anti‐TNFα therapies, notably infliximab, in RA , psoriatic arthritis and ankylosing spondylitis , which suggests that fat mass may affect the response to biologic agents. Conversely, two recent studies showed that response to TCZ in patients with RA was not affected by baseline BMI . We focused on the relationship between BMI and response to ABA in RA treatment and found no association of increased BMI and low response to ABA.…”
Section: Discussionmentioning
confidence: 74%
“…(68) We found that the studies involving TNF-α inhibitors were associated with different outcomes: four studies (2,10,16,17) were associated with positive outcomes, three studies (25,26,29) with neutral outcomes and ten studies (11,(32)(33)(34)40,55,56,61,62,65) with negative outcomes. Rituximab was associated with positive, (17) neutral (23) and negative (11,56) outcomes, while tocilizumab was similarly associated with positive, (15) neutral (22,27) and negative (11,56) outcomes. Due to the limited number of studies for tocilizumab, we conducted an additional literature search on it and found that tocilizumab is unlikely to be affected by obesity.…”
Section: Discussionmentioning
confidence: 91%
“…A total of 11 studies with 3,834 subjects showed that obesity was neither associated with better nor worse outcomes, with insignificant associations reported (Table II). (6,8,(22)(23)(24)(25)(26)(27)(28)(29)(30) Most of the studies investigated the RA disease population. For PsA and axial SpA (AxSpA), one study was found for each disease population.…”
Section: Neutral Association With Outcomementioning
confidence: 99%
“…43 There is no evidence for an effect of BMI on response to tocilizumab treatment in RA. 69,70 One study of 204 patients with RA could not find an effect of current smoking on EULAR response after 24 weeks of tocilizumab treatment. 43 PREDICTORS OF RESPONSE TO ABATACEPT TREATMENT There are only a few studies exploring biomarkers predictive of response to abatacept.…”
Section: Predictors Of Response To Tocilizumab Treatmentmentioning
confidence: 99%